2016
DOI: 10.5578/khj.10344
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Elevated HbA1c and Deep Sternal Wound Infection in Patients Undergoing Cardiac Surgery

Abstract: Introduction: Hyperglycemia is common in patients with and without diabetes mellitus (DM) following cardiac surgery. Intra-and postoperative hyperglycemia has been shown to be an independent risk factor for deep sternal wound infection (DSWI) after cardiac surgery. However, whether the preoperative chronic glycemic control is associated with the risk of DSWI remains controversial. Hemoglobin A1c (HbA1c) provides a measure of glucose control over the prior 2-3 months. The aim of this study was to evaluate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…KLF4 has been reported to physically bind to the active subunit P65 of transcription factor NF-κB in vascular endothelial cells to prevent the nuclear translocation of P65, thereby exerting its anti-inflammatory role by inhibiting the transcriptional activation on downstream inflammatory factors of P65 [ 22 ] . In endothelial cells and immune cells, P300 can bind with the active subunit P65 of NF-κB to induce acetylation of P65, thereby promoting the transcriptional activation on downstream inflammatory factors by P65 [ 23 ] . Overexpressed KLF4 can competitively bind to P300, inhibiting the binding of P300 with P65 to attenuate its transcriptional activity, subsequently exerting an anti-inflammatory effect [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…KLF4 has been reported to physically bind to the active subunit P65 of transcription factor NF-κB in vascular endothelial cells to prevent the nuclear translocation of P65, thereby exerting its anti-inflammatory role by inhibiting the transcriptional activation on downstream inflammatory factors of P65 [ 22 ] . In endothelial cells and immune cells, P300 can bind with the active subunit P65 of NF-κB to induce acetylation of P65, thereby promoting the transcriptional activation on downstream inflammatory factors by P65 [ 23 ] . Overexpressed KLF4 can competitively bind to P300, inhibiting the binding of P300 with P65 to attenuate its transcriptional activity, subsequently exerting an anti-inflammatory effect [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are some reports that investigated the development of DSSI in patients undergoing open-heart surgery [ 11 , 23 ] . Sevük et al [ 23 ] stated that there was no relationship between high perioperative HbA1c and DSSI, and that there was no increase in the frequency of DSSI development in patients with adequate perioperative glycemic control. Similarly, Kuhl et al [ 17 ] reported that they found no relationship between HbA1c level in perioperative mortality and DSSI development.…”
Section: Discussionmentioning
confidence: 99%
“…On contrast, other studies suggested that there is no strong relationship between elevated HbA1c% and SSI after CABG such as study carried out by Hudson and associateswhoexamined 1.474 patients found no association between elevated HbA1c and infection after cardiac surgery. However they found that Thirty-day mortality and acute kidney injury were significantly higher in patients with HbA1c>6% [16] Sevükand colleagesindicated that elevated HbA1c levels in the preoperative period is not a risk factor for DSWI in patients undergoing CABG while good perioperative glycemic control decreases incidence of DSWI [3] . In Offpump coronary artery bypass(OPCAB) patients with poorly controlled DM (HbA1c > 6.5) SSI was not related to elevated HbA1c levels as reported by Matsuura and cowrkers [16] .…”
Section: Discussionmentioning
confidence: 99%
“…The glycosylated hemoglobin (HbA1c %) is a sensitive and reliable biomarker that provides a measure of glucose control status over the prior 2-3 months. TheADA (American Diabetes Association) suggests an HbA1c goal of less than 7% to reduce long-term complications of DM [3] . Superficial wound infection (SWI) involves only the skin or subcutaneous tissue [4] .Deep Sternal Wound Infection (DSWI) involves the muscle, bone, pericardium, and/or mediastinum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation